Parental beliefs on children's play: comparison among mainland Chinese, Chinese immigrants in the USA, and European-Americans. Issue 3 (3rd March 2016) - Jiang, Shan; Han, Myae
Abstract : The current study surveyed parental play beliefs among the three groups of parents: the mainland Chinese, Chinese immigrants in the USA, and European-Americans. Limited comparison studies on parental play beliefs were previously reported for these three populations in the literature. Two measures, the Chinese child-rearing ideology and parental play beliefs scale, were used in this study. Responses from 144 responses were collected. The mainland Chinese parents reported similar scores both in the Chinese child-rearing ideology and in play beliefs as to the European-American parents. Surprisingly, the Chinese immigrant parents reported the highest scores in the Chinese child-rearing ideology and the lowest scores in the parental play beliefs among the three groups. This indicated that the surveyed Chinese immigrant parents held more traditional Chinese child-rearing ideology and were less positive towards children's play.